2007
DOI: 10.1021/ar600037c
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel-Derived Spheres for Spherical Microcavity

Abstract: Encapsulation of light to small spheres ensures the highest quality factor ( Q factor) to enhance the interaction between light and materials. In this Account, we describe the fabrication of micrometer-sized spherical particles of organic-inorganic hybrid materials to study the potential ability as a spherical cavity laser. The spherical particles prepared by the vibrating orifice technique included those of nondoped and doped with organic dyes and rare-earth-metal ions, and some of them were cladded with low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“… Thresholds of laser emission in various small‐sized resonators: fiber lasers (R) 3,4 ; waveguide lasers (Nd 3+ ) 6 ; glass sphere lasers pumped by direct pumping, 19 half‐polished fiber coupler (R and Nd 3+ ), 17 terrace (R), 8,23 and taper fibers (R). 15 (R) and (Nd 3+ ) represent stimulated Raman emission and laser emission due to Nd 3+ .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Thresholds of laser emission in various small‐sized resonators: fiber lasers (R) 3,4 ; waveguide lasers (Nd 3+ ) 6 ; glass sphere lasers pumped by direct pumping, 19 half‐polished fiber coupler (R and Nd 3+ ), 17 terrace (R), 8,23 and taper fibers (R). 15 (R) and (Nd 3+ ) represent stimulated Raman emission and laser emission due to Nd 3+ .…”
Section: Discussionmentioning
confidence: 99%
“…Spherical resonators have potential uses, such as a multiwavelength laser, a low threshold laser, and optical signal processors. A brief history of spherical cavity lasers has been summarized in our previous report 8 . The first trial of laser action in spherical resonator was reported in Sm 2+ ‐doped CaF 2 spheres of millimeter size in 1961 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, a micrometer-sized spherical cavity laser having a terrace-shaped pumping light entrance was investigated [10][11][12]. A terrace portion was formed on microspheres of multicomponent glasses (n D ¼ 1:93) several tens of micrometers in diameter using organic-inorganic hybrid materials (n D ¼ 1:45) in the binary system of 3-methacryloxypropyltrimethoxysilane (MOPS) and tetramethoxysilane (TMOS).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore efficient coupling technique to the multicomponent glass spheres is required for practical devices. In our previous works, micrometer-size spherical cavity laser having a terrace-shaped pumping light entrance was investigated [10][11][12]. Terrace portion was formed on the microspheres of multi-component glasses (n D =1.93) of several tens of micrometers in diameter by using organicinorganic hybrid materials (n D =1.45) in the binary system of 3-methacryloxypropyltrimethoxysilane (MOPS) and tetramethoxysilane (TMOS).…”
Section: Introductionmentioning
confidence: 99%